INVESTIGATION ON THE MECHANICALBEHAVIOUR OF THE GLASS/ BANANAFIBERS REINFORCED EPOXY COMPOSITE - Nagendra B R; K S Ravi; Dr. G V Naveen prakash (International Journal of Innovations in Engineering Research and Technology, 2021)
The composites are one of the advanced engineering materials which are commonly used in this decade in day today life. The natural fibers are used for the reinforcement in order to get higher strength, reduced density, lower weight for several applications. The hybrid composite is obtained by using two or more materials with varying properties. Hybridization is a process of incorporating synthetic fiber with the natural fiber to get the better strength, stiffness, high strength to weight ratio and improvements in the mechanical properties. In this work, an attempt is made to hybridize using Glass (synthetic) fiber as well as Banana (natural) fiber with Epoxy resin as the matrix material, such that to reduce the overall use of the synthetic reinforcement and to enhance the mechanical properties. T